Molecular and Functional Characterization of α Chain of Interleukin-15 Receptor (IL-15Rα) in Orange-Spotted Grouper (Epinephelus coioides) in Response to Vibrio harveyi Challenge - Yilin Zhang; Fan Wu; Guanjian Yang; Jichang Jian; Yishan Lu; Zhiwen Wang (Animals, 2023)
Interleukin-15 (IL15) is a proinflammatory cytokine that could induce the production of inflammatory cytokines. In this study, the α chain of the IL15 receptor of Epinephelus coioides (Ec-IL15Rα), a natural regulator of IL15, was identified, and immune response functions of fish were determined and characterized. Ec-IL15Rα contains a 720 bp open reading frame that encodes 239 amino acids, including four typical conserved cysteine residues with a highly conserved sushi domain. Ec-IL15Rα is closely related to Epinephelus lanceolatus and is the most clustered with teleost. Subcellular localization studies showed that Ec-IL15Rα was situated in the cytoplasm and cell membrane. Ec-IL15Rα was detected in 11 tissues, with the highest expression in the liver and blood. Meanwhile, the Ec-IL15Rα transcriptional levels substantially increased in nine tissues after Vibrio harveyi infection. Ec-IL15Rα was significantly up-regulated in HKLs by ConA, PHA, LPS and poly I:C stimulation. In vitro analysis, the recombinant protein of rEc-IL15Rα stimulates HKL proliferation and IL1R, IL6R, IL10, and IL16 expression. Challenge experiments revealed that IL15Rα protein showed an increase of 6.67–10% survival protection rate after V. harveyi infection. This study provides a better understanding of the immune protection of IL15Rα in vertebrate fish.